2020
DOI: 10.1108/ijdi-06-2020-0123
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive abilities and income: preliminary evidence from a developing country

Abstract: Purpose Related literature finds that human capital proxied by cognitive abilities is an important antecedent of numerous specific life outcomes. The purpose of this study is to extend existing evidence by investigating the link between cognitive skills and income in Tajikistan. Tajikistan is a landlocked low-income country situated in Central Asia. Its population is 9.1 million people and gross domestic product per capita of US$822. According to the World Bank, Tajikistan has made significant progress in decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Lynn and Vanhanen Vanhanen, 2002, 2006) reported a correlation of -0.59 between IQ and corruption. Similarly, some other studies have reported that high cognitive abilities (IQ) predict lower corruption perceptions (Achim et al, 2021;Farzanegan, 2020;Potrafke, 2012;Salahodjaev and Malikova, 2021). According to the findings of the present study, IQ has a strong negative correlation (r ¼ -0.63) to corruption when GDP per capita was not controlled.…”
Section: Individual Difference Factors and Corruptionsupporting
confidence: 85%
“…Lynn and Vanhanen Vanhanen, 2002, 2006) reported a correlation of -0.59 between IQ and corruption. Similarly, some other studies have reported that high cognitive abilities (IQ) predict lower corruption perceptions (Achim et al, 2021;Farzanegan, 2020;Potrafke, 2012;Salahodjaev and Malikova, 2021). According to the findings of the present study, IQ has a strong negative correlation (r ¼ -0.63) to corruption when GDP per capita was not controlled.…”
Section: Individual Difference Factors and Corruptionsupporting
confidence: 85%
“…Lynn and Vanhanen ( Lynn and Vanhanen, 2002 , 2006 ) reported a correlation of -0.59 between IQ and corruption. Similarly, some other studies have reported that high cognitive abilities (IQ) predict lower corruption perceptions ( Achim et al., 2021 ; Farzanegan, 2020 ; Potrafke, 2012 ; Salahodjaev and Malikova, 2021 ). According to the findings of the present study, IQ has a strong negative correlation (r = -0.63) to corruption when GDP per capita was not controlled.…”
Section: Discussionmentioning
confidence: 64%